REVITALISASI MATA PENCAHARIAN DI LAHAN GAMBUT: KERAJINAN ANYAMAN DARI PURUN SEBAGAI SALAH SATU BENTUK USAHA BERKELANJUTAN DI KABUPATEN OGAN KOMERING ILIR (OKI), SUMATERA SELATAN - Bunga Karnisa Goib; Nadia Fitriani; Satrio Adi Wicaksono; Muhammad Yazid; Dessy Adriani (Centre for Research and Development on Social, Economy, Policy and Climate Change, 2019)
This study is conducted to better understand the potential of purun weaving as a suitable business approach that could support peatland restoration in South Sumatra. It aims to analyze the obstacles of purun weaving and its market potential as green products. This study applies qualitative and quantitative methods, including in-depth interviews and surveys. The in-depth interviews invove local business actors in Pedamaran Sub-district, Ogan Komering Ilir Regency (i.e. harvesters, weavers, and traders) and the policy-makers. Online and intercept surveys are conducted to analyze current condition and market potential of purun handicrafts, especially as the example of green products. Identified challenges include lack of market knowledge and connections, unstable supply of raw materials, lack of financial capitalization, and low product quality. The market potential for green products, however, is highly promising, as more than 80% of respondents are willing to pay a higher price for these products. Gaps between existing production system and market potential could be narrowed down by adjusting policies for existing peat swamp areas, improving access to microfinance, and implementing specific capacity building for the weavers. Moreover, suitable marketing strategies are required to support the business sustainability of purun weaving.